The Cxcr2+ subset of the S100a8+ gastric granylocytic myeloid-derived suppressor cell population (G-MDSC) regulates gastric pathology - Kao, Krystal D.; Grasberger, Helmut; El-Zaatari, Mohamad (Frontiers in Immunology, 2023)
Introduction Gastric myeloid-derived suppressor cells (MDSCs) are a prominent population that expands during gastric pre-neoplastic and neoplastic development in humans and mice. However, the heterogeneity of this population has circumvented the ability to study these cells or understand their functions. Aside from Schlafen-4+ (Slfn-4+) MDSCs in mouse studies, which constitute a subset of this population, limitations exist in characterizing the heterogeneity of the gastric CD11b+Ly6G+ population and targeting its different subsets. Here we identify S100a8 as a pan-specific marker for this population and utilize it to study the role of the S100a8+Cxcr2+ subset. Methods We profiled gastric CD11b+Ly6G+ versus CD11b+Ly6G- myeloid cells by transcriptomic and single-cell RNA sequencing. We identified S100a8 as a pan-specific marker of the gastric granulocytic MDSC (G-MDSC) population, and generated S100a8CreCxcr2flox/flox to study the effects of Cxcr2 knockdown. Results Following 6-months of Helicobacter felis infection, gastric CD11b+Ly6G+ G-MDSCs were highly enriched for the expression of S100a8, S100a9, Slfn4, Cxcr2, Irg1, Il1f9, Hcar2, Retnlg, Wfdc21, Trem1, Csf3R, Nlrp3, and Il1b. The expression of these distinct genes following 6mo H. felis infection marked heterogeneous subpopulations, but they all represented a subset of S100a8+ cells. S100a8 was identified as a pan-marker for CD11b+Ly6G+ cells arising in chronic inflammation, but not neutrophils recruited during acute gut infection. 6mo Helicobacter felis-infected S100a8CreCxcr2flox/flox mice exhibited worsened gastric metaplastic pathology than Cxcr2flox/flox mice, which was associated with dysregulated lipid metabolism and peroxidation. Conclusion S100a8 is a pan-specific marker that can be used to target gastric G-MDSC subpopulations, of which the Cxcr2+ subset regulates gastric immunopathology and associates with the regulation of lipid peroxidation.